Measurement of the total flux averaged neutrino induced neutral current elastic scattering cross section with the T2K Pi-Zero detector - Ruterbories, Daniel, author; Berger, Bruce E., advisor; Buchanan, Norman, committee member; Lear, Kevin, committee member; Wilson, Robert, committee member (Colorado State University. Libraries, 2014)
Tokai-to-Kamioka (T2K) is a second generation accelerator neutrino oscillation experiment. T2K uses a high intensity proton beam produced at the Japan Proton Accelerator Research Complex (J-PARC) incident on a carbon target and focused with three magnetic horns to produce a high intensity and nearly pure muon neutrino beam with a peak energy of 600 MeV at a 2.5º axis angle. The muon neutrino beam travels 295 km across Japan to the Super Kamiokande (SK) water Cherenkov detector in the Kamioka mine. The neutrino beam is also sampled by a complex of near detectors 280 m downstream of the carbon target located both on and off the beam axis. These detectors measure the neutrino beam before neutrino oscillations occur to provide input constraints to oscillation searches using SK. The off-axis near detector, ND280, is a composite detector made up of a tracker section and a Pi-Zero detector (PØD), all surrounded by an electromagnetic calorimeter. The entire detector is enclosed in a dipole magnet with a field of 0.2 T. The primary purpose of the tracker section is to measure neutrino induced charged current events characterized by the production of muons. The PØD is primarily designed to detect electromagnetic showers and to measure interactions on water through the use of a removable water target. In addition to these measurements, the ND280 detector is also used to study the cross sections of neutrino interactions on the various materials in the detectors. Limited knowledge of the cross sections in this neutrino energy regime are an important source of systematic error in neutrino oscillation measurements. This thesis presents a measurement of one neutrino interaction channel in the PØD, neutral current elastic scattering (NCE). In this process a neutrino elastically scatters off a proton or neutron in the target nucleus producing a proton or neutron with higher energy. The signature of this process is a single proton track. A particle identification algorithm (PID) was developed to suppress the dominant muon background. Using this algorithm in conjunction with a Michel electron veto the flux averaged absolute cross section is measured to be <σ>flux =2.24×10-39 cm2,nucleon ±0.07(stat.) +0.53,-0.63 (sys.).
Keywords: cross section; elastic; ND280; neutral current; neutrino; T2K